Novel Antimicrobial Topical Gel That Exhibits Inhibitory Effectiveness Toward Common Microbes in Wound Infection (P19-007-19). (13th June 2019) - Clark, W Andrew; Ford, Rachel; Vance, Lindsey; Morley, Lexis; Stovall, Thomas; McHale, Leah; Raley, Danny; Fox, Sean
Abstract: Objectives: This research project focused on the inhibitory effectiveness of a novel antimicrobial gel (AMG) towards a panel of common microbes involved in wound infections. Methods: A novel antimicrobial topical gel consisting of vitamin E TPGS (tocopherol polyethylene glycol succinate), ascorbyl palmitate, zinc aspartate, lavender oil and deionized distilled water was developed in our laboratory. Various in vitro techniques were used to determine the effectiveness of AMG on prokaryotic and eukaryotic microbes. Results: In vitro experiments show that while AMG had varying inhibitory effects on both prokaryotic and eukaryotic microbes, there was a predilection for AMG to inhibit planktonic growth and biofilm formation of Staphylococcus species, most notably Methicillin Resistant Staphylococcus aureus (MRSA). The inhibitory effect of the AMK on planktonic growth was immediate with a four-fold reduction in growth, compared to controls, within 4 to 6 hrs of induction. Within 24 hrs S. aureus growth was minimal and complete inhibition of growth was achieved within 48 hrs. In an in vitro biofilm model, the AMG inhibited Staphylococcus biofilm attachment by 67% (density), 82% (mass) and 95% (viability). On pre-formed established biofilms, the AMG was able to inhibit 47% (density), 47% (mass) and 44% (viability) Staphylococcus biofilms. Antibiotic comparison experiments demonstrated that the MIC (minimum inhibitory concentration) of Mupirocin was <1% while the AMG was slightly elevated at <2%. However, thus far, Staphylococcus has not demonstrated resistance to AMG whereas it has become a troubling concern for Mupirocin. Fluorescent microscopy using LIVE/DEAD (SYTO9/propidium iodide) staining of Staphylococcus culture controls exhibited robust growth and viability while AMG treated Staphylococcus cultures showed sparse growth of non-viable cells. AMG has inhibitory activities against normal and methicillin resistant S. pseudintermedius which are prevalent in lick granulomas in canines. Conclusions: AMG is nontoxic to humans and canines and demonstrates potential for use in wound infections as an alternative to commonly prescribed antibiotics without the unintended drug resistance seen with antibiotics. AMG is an effective treatment option, this far in vitro, for Staphylococcus infections that are particularly prone to biofilm growth. Funding Sources: ETSU, Honors College, Student/Faculty Collaborative Research Grant.